Toolkit for social responsibility of business in the system of inclusive corporate management of sustainable development of Ukrainian agricultural companies - Степаненко, С. В.; Немашкало, К. Р.; Саліонович, Л. М. (Baltic Journal of Economic Studies, 2023)
The research subject is the social responsibility of agribusinesses in the context of current corporate governance practices. Methodology. The study uses the following methods of economic research: content analysis method (when processing scientific sources and reviewing thematic literature); abstract and logical method (when substantiating the defining principles and criteria of social responsibility of business entities in the agricultural sector); statistical observations and economical and statistical calculations (when analysing indicators of the achieved state of social responsibility of agricultural companies); abstract and logical method (when substantiating conclusions to the study). The research is aimed at finding tools to increase the social responsibility of agrarian business through the transformation of the corporate culture of agriculturalmanagement of Ukrainian companies. Conclusion. Ukraine has a strong agricultural potential. However, achieving national and global sustainable development goals, which are relevant shortly, requires a change in business values and strategic guidelines. Such values should be aimed at solving the problems of protecting the environment, preserving natural resources, improving the quality and safety of agri-food products, and improving the quality of life of the rural population. The solution to these problems is inextricably linked to voluntary, socially responsible agribusiness initiatives. The analysis carried out showed that there is a high level of agribusiness social responsibility in the management of the activities of large-scale agricultural enterprises in Ukraine, which is reflected in the voluntary non-financial reports. In small- and medium-sized agribusinesses, the perception of the need for social responsibility is limited and constrained by a lack of financial resources. The calculated indicators show a low level of social responsibility in the agricultural business of small- and medium-sized agricultural enterprises in Ukraine. The level of chemicalisation of agricultural production and ploughing of agricultural land is high. There are significant problems with the use of rural labour resources and the development of rural areas. The main problems were identified in the spectrum of irrational use of land and labour resources and the low quality of life of the population in rural areas of Ukraine. The processes of recognition of the values and benefits of socially responsible agribusiness in Ukraine are slow. As a tool for increasing the social responsibility of agribusinesses in Ukraine, a system of principles and criteria of socially responsible business is proposed for implementation in the corporate governance of Ukrainian agribusinesses.
Інструментарій соціальної відповідальності бізнесу в системі інклюзивного корпоративного управління сталого розвитку українських аграрних компаній
Web of Science
Keywords: agricultural business; inclusive agricultural management; Ukrainian agricultural companies; social responsibility; corporate culture; sustainable development